Training to Serve: CoMACS and the Application of Ignatian Pedagogy in the Training of Healthcare Professionals in Spain. - Gutierrez-Aguirregabiria, Ane; Romero-Yesa, Susana; Sánchez-Isla, José Ramón (Journal of Religion & Health, 2026)
The University of Deusto, a Jesuit institution with a long educational tradition, bases its pedagogical model on Ignatian Pedagogy, promoting the comprehensive education of students. Within this framework, transversal learning outcomes occupy a central place, with the hallmark skill being that which develops self-knowledge, ethics, social responsibility, sustainability, and openness to transcendence. This approach seeks to train students who are committed to society and capable of acting with professional excellence and a sense of social justice. In this context, the Faculty of Health Sciences was created in 2020 with the mission of training professionals in Medicine, Nursing, Physiotherapy, and Psychology who not only master technical skills but also essential transversal learning outcomes. To achieve this, priority is given to the application of active learning methodologies such as Problem-Based Learning (PBL), Clinical Scenario-Based Learning (CSBL), and simulation, all of which are aligned with Ignatian Pedagogy. To support this teaching innovation, the Commission on Learning Methodologies in Health Sciences (CoMACS, from the Spanish) was established as a natural evolution of the Medical and Health Education Unit. Its objective is to coordinate the implementation of these methodologies, train faculty, and ensure educational quality. Its achievements include the full implementation of PBL in the Bachelor's Degree in Medicine, the consolidation of CSBL in the Bachelor's Degree in Nursing, and the development of simulation programs. This model has strengthened teaching innovation and educational excellence, positioning itself as a benchmark at the University of Deusto.